2021
DOI: 10.3390/ijms221810009
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Targeting Innate Immune Cells in Tumor Microenvironment

Abstract: A variety of innate immune cells such as macrophages, dendritic cells, myeloid-derived suppressor cells, natural killer cells, and neutrophils in the tumor microenvironments, contribute to tumor progression. However, while several recent reports have studied the use of immune checkpoint-based cancer immunotherapy, little work has focused on modulating the innate immune cells. This review focuses on the recent studies and challenges of using nanoparticles to target innate immune cells. In particular, we also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 157 publications
(178 reference statements)
0
12
0
Order By: Relevance
“…Determining appropriate immunotherapy treatment plans for cancer patients now relies significantly on the detection of immune cells that can serve as biomarkers in the cancer immunological microenvironment. The quantity of immune cells and how they are distributed is the single most critical element in determining the eventual course of a tumor, including whether or not it will inhibit or promote carcinogenesis, cell metastasis, cell migration, and tumor angiogenesis [36,37]. Nevertheless, 7 Disease Markers the immunological microenvironment in the many forms of cancer is intricate and heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Determining appropriate immunotherapy treatment plans for cancer patients now relies significantly on the detection of immune cells that can serve as biomarkers in the cancer immunological microenvironment. The quantity of immune cells and how they are distributed is the single most critical element in determining the eventual course of a tumor, including whether or not it will inhibit or promote carcinogenesis, cell metastasis, cell migration, and tumor angiogenesis [36,37]. Nevertheless, 7 Disease Markers the immunological microenvironment in the many forms of cancer is intricate and heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tumor immune microenvironment (TIME), nanomaterials can be used to modulate the immunosuppressive tumor microenvironment by targeting tumor-associated macrophages (TAMs), regulatory T cells (Treg cells), regulatory B cells, myeloid-derived suppressor cells (MDSCs), as well as cancer-associated fibroblasts. Several nanoparticle-based strategies that target TAMs for suppressing tumor progression include TAM depletion, inhibiting monocyte recruitment, and TAM reprogramming[ 25 ]. Recent studies showed that the utilization of dendrimer nanoparticles carrying the chemotherapeutic methotrexate that specifically recognize the folate receptor-2, which is overexpressed in TAMs, increases therapeutic efficacy by depleting TAMs[ 25 ].…”
Section: Types Of Cancer Nanomedicinesmentioning
confidence: 99%
“…Several nanoparticle-based strategies that target TAMs for suppressing tumor progression include TAM depletion, inhibiting monocyte recruitment, and TAM reprogramming[ 25 ]. Recent studies showed that the utilization of dendrimer nanoparticles carrying the chemotherapeutic methotrexate that specifically recognize the folate receptor-2, which is overexpressed in TAMs, increases therapeutic efficacy by depleting TAMs[ 25 ]. Considering monocyte recruitment, it is reported that silver nanoparticles have an adjuvant effect inducing recruitment and activation of local macrophages[ 26 ].…”
Section: Types Of Cancer Nanomedicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…TME with specific antibody to potentially alleviate adverse effects(106). In addition to eliminating inhibitory signals in the TME, improving the immunogenicity of tumor cells to enhance CTL function is also an important strategy for immunotherapy.…”
mentioning
confidence: 99%